Efficiency of the new fractional derivative with nonsingular Mittag-Leffler kernel to some nonlinear partial differential equations - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa; Baleanu, Dumitru (Pergamon-Elsevier Science Ltd, 2018)
In this work, the efficiency of the Atangana-Baleanu (AB) derivative over Caputo-Fabrizio (CF) to some nonlinear partial differential equation is presented. The considered equations are Rosenou-Haynam equation (RHE) and a class of mKdV (CmKdV) equation. The effective and efficient technique called the fractional homotopy perturbation transform method (FHPTM) is applied for the investigation of the governing equations. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Fractional RHE; Fractional CmKdV; AB derivative; CF; FHPTM; Numerical simulations